VeRidium: A Fully Immersive and Interactive Virtual Reality Educational Environment - Thiele, Günther; Mirica, Katherine A.; Habig, Sebastian (Journal of Chemical Education, 2025)
We present VeRidium, a fully immersive and interactive virtual reality environment for the utilization in university-level teaching. In a comparative study, one cohort of students was revisiting the fundamental structures of the metals in the virtual environment, another cohort was given the same tasks with clay models. Pre-Post-Test analyses reveal the efficacy and strengths of the virtual environment despite a larger preparational effort. Some lessons-learned are given from our journey starting with the programming of the environment from scratch, to final upload in the app store and implementation in lecture hall
Keywords: Introductory Chemistry; First-Year Undergraduate; Second-Year Undergraduate; Upper-Division Undergraduate; Graduate Education; Inorganic Chemistry; Computer-Based Learning; Hands-On Learning; Assessment; Multimedia-Based Learning; Atomic Structure; Crystals; Materials Science; Metals; Solid State Chemistry